A model of the professional field as the basis for an adaptive educational process - I. I. Shpak; S. N. Kasanin (Informatika)
Objectives. The main purpose of the work is to study the advantages of an activity-based approach, or functional approach in comparison with a subject-based approach, or lecture-based approach for creating a model of a professional field for adaptive educational process. The relevance of the problem being solved is caused by due to the fact, that adaptive educational technologies, thanks to the extensive computerization and informatization of all spheres of human activity, as well as the innovative development of artificial intelligence, have become dominant in teaching systems at all levels, from preschool to higher education institutions. Without a highly effective model of the professional field, it is impossible to successfully implement adaptive learning.Methods. To achieve the goals and to prove the statements formulated, the method of comparative analysis of the most widely used ways for creating models of the professional field for adaptive learning in modern systems, was used. To do this, we studied: the effectiveness of using the traditional approach, which is based on subjectspecific or lecture-seminar signs of structuring educational material; as well as the effectiveness of using an activity-based approach based on the concept of "Modules of labor competencies" for the formation of educational material.Results. The analysis of the quality of educational material (a model of a professional field for an adaptive educational process) obtained using the traditional approach, and educational material (the same model for its intended purpose) obtained on the basis of an activity approach in accordance with the concept of "Modules of labor competencies". The results of the analysis are compared and theoretical statements are summarized, taking into account the examples of developed modular materials, as well as the pilot implementation of previously developed modular programs.Conclusion. The information given in the article can be useful for specialists, researchers and heads of educational institutions of various levels, when planning and creating adaptive learning systems. The conclusions and recommendations fully comply with the requirements of the development of the education system of the Republic of Belarus.